A ribosomal RNA fragment with 2′, 3′-cyclic phosphate and GTP-binding activity acts as RIG-I ligand. Issue 18 (18th September 2020) - Jung, Stephanie; von Thülen, Tina; Yang, Ines; Laukemper, Viktoria; Rupf, Benjamin; Janga, Harshavardhan; Panagiotidis, Georgios-Dimitrios; Schoen, Andreas; Nicolai, Marina; Schulte, Leon N; Obermann, Hannah-Lena; Weber, Friedemann; et al.
Abstract: The RNA helicase RIG-I plays a key role in sensing pathogen-derived RNA. Double-stranded RNA structures bearing 5′-tri- or diphosphates are commonly referred to as activating RIG-I ligands. However, endogenous RNA fragments generated during viral infection via RNase L also activate RIG-I. Of note, RNase-digested RNA fragments bear a 5′-hydroxyl group and a 2′, 3′-cyclic phosphate. How endogenous RNA fragments activate RIG-I despite the lack of 5′-phosphorylation has not been elucidated. Here we describe an endogenous RIG-I ligand (eRL) that is derived from the internal transcribed spacer 2 region (ITS2) of the 45S ribosomal RNA after partial RNase A digestion in vitro, RNase A protein transfection or RNase L activation. The immunostimulatory property of the eRL is dependent on 2′, 3′-cyclic phosphate and its sequence is characterized by a G-quadruplex containing sequence motif mediating guanosine-5′-triphosphate (GTP) binding. In summary, RNase generated self-RNA fragments with 2′, 3′-cyclic phosphate function as nucleotide-5′-triphosphate binding aptamers activating RIG-I.